2009
DOI: 10.1186/1475-2859-8-54
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the role of phosphotransacetylase (pta) and the acetate/acetyl-CoA node in Escherichia coli

Abstract: Background: Acetate metabolism in Escherichia coli plays an important role in the control of the central metabolism and in bioprocess performance. The main problems related to the use of E. coli as cellular factory are i) the deficient utilization of carbon source due to the excretion of acetate during aerobic growth, ii) the inhibition of cellular growth and protein production by acetate and iii) the need for cofactor recycling (namely redox coenzymes and free CoASH) to sustain balanced growth and cellular ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
75
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 61 publications
7
75
1
3
Order By: Relevance
“…Improving the cell density of bovine E. coli would enhance the applicability of the vaccine to the cattle industry. The cell density is limited by acetate, a primary inhibitory metabolite that accumulates in E. coli cultures, which was caused of acetate inhibition for DNA transcription, RNA translation, protein stability and compound synthesis [3] . The acetate accumulation can be reduced by optimizing the culture conditions and genetically modifying the cells [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the cell density of bovine E. coli would enhance the applicability of the vaccine to the cattle industry. The cell density is limited by acetate, a primary inhibitory metabolite that accumulates in E. coli cultures, which was caused of acetate inhibition for DNA transcription, RNA translation, protein stability and compound synthesis [3] . The acetate accumulation can be reduced by optimizing the culture conditions and genetically modifying the cells [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli, acetate is formed via two pathways: the phosphotransacetylaseacetate kinase (Pta-AckA) pathway and the pyruvate oxidase B (PoxB) pathway, which use acetyl-CoA and pyruvate as substrate, respectively [7,8] . Conversely, reducing the carbon flux in the Embden-Meyerhof pathway (EMP) reducing of the acetate excretion by lowering the pyruvate production [3,9] . Acetate synthesis and its metabolic flux distribution are affected from the values of the culture parameters [8,10] .…”
Section: Introductionmentioning
confidence: 99%
“…[12] The excretion of acetate results in deficient utilization of carbon sources and inhibition of cellular growth and protein production. [13] Many studies have reported a highyield production of recombinant proteins obtained by reduction of the acetate accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Many studies have reported a highyield production of recombinant proteins obtained by reduction of the acetate accumulation. [12] The pathways of phosphotransacetylaseÀacetate kinase (PtaÀAckA)…”
Section: Introductionmentioning
confidence: 99%
“…This specific aspect makes it in principle possible to describe strains with different "acetate overflow lines" (e.g. mutants [37,38] or "acetate feeding" strains obtained in evolution experiments [39,40]), which correspond to feasible -albeit suboptimalcellular states that would be harder to describe by the model of [13]. On the other hand, the latter characterizes, in a sense, The respiration phenotype has a large yield (small q) and large specific protein costs, while the fermentation phenotype carries lower yields (higher q) and a smaller cost.…”
mentioning
confidence: 99%